Multidimensional Picture of Public Political Participation in Bondowoso Regency - Rizkika, Haressa Lintang; Mukid, Zainul; Chusairi, Achmad; Muhammady, Iffan Gallant El (POLITICO, 2024)
This study aims to describe the level of multidimensional political participation of the community in Bondowoso Regency. Data were collected from 92 respondents with the criteria of Bondowoso residents and had participated in political activities, especially the Election. Indicators of political participation are: trust, awareness, knowledge, and political participation. In this study, the adoption of previously validated political participation measurement tools was used to ensure the reliability and validity of the results obtained. This measurement tool was adapted from previous studies related to political participation in Indonesia, with adjustments to the local context of Bondowoso. The results of the descriptive analysis showed that the majority of respondents showed low to moderate levels of political trust, and political knowledge that was generally in the moderate category. The low political participation found in this study also shows that although the community has quite good political awareness, it is not enough to encourage more active political participation without strong trust in political institutions. However, this study has several limitations, including a limited sample size and potential bias in the measurement instrument. For future research, it is recommended to expand the sample size, develop more valid instruments, and consider broader contextual factors to explore more deeply the dynamics of political participation and community perceptions of the local political process.